Preference of neuromuscular patients regarding equipment for daytime mouthpiece ventilation: A randomized crossover study. (18th December 2019) - Toussaint, Michel; Chatwin, Michelle; Verhulst, Stijn; Reychler, Gregory
Abstract: Background: Patients with neuromuscular disorders (NMDs) are likely to develop respiratory failure which requires noninvasive ventilation (NIV). Ventilation via a mouthpiece (MPV) is an option to offer daytime NIV. Objectives: To determine the preferred equipment for MPV by patients with NMDs. Methods: Two MPV equipment sets were compared in 20 patients with NMDs. Set 1, consisted of a non‐dedicated ventilator for MPV (PB560, Covidien) with a plastic angled mouthpiece. Set 2, consisted of a dedicated MPV ventilator (Trilogy 100, Philips Respironics) without backup rate and kiss trigger combined with a silicone straw mouthpiece. The Borg dyspnea score, ventilator free time, transcutaneous oxygen saturation (SpO2) and carbon dioxide tension (TcCO2 ) were recorded with and without MPV. Patient perception was assessed by a 17‐items list. Results: Carbon dioxide tension measurements and total perception score were not different between the two MPV sets. Dyspnea score was lower with the non‐dedicated versus dedicated equipment, 1 (0.5) versus 3 (1‐6), P < 0.01. All patients with a ventilator free time lower than 6 hours preferred a set backup rate rather than a kiss trigger. Sixty five percent of patients preferred the commercial arm support and 55% preferred the plastic angled mouthpiece. Conclusions: Dedicated and non‐dedicated MPV equipment are deemed effective and comfortable. Individualization of arm support and mouthpiece is advised to ensure success of MPV. A ventilator free time lower than 6 hours seems to be a useful indicator to a priori set a backup rate rather than a rate at zero associated to the kiss trigger.